The Fractional Kalman Filter-Based Asynchronous Multirate Sensor Information Fusion. (5th December 2018) - Xue, Guangyue; Xu, Yubin; Guo, Jing; Zhao, Wei
Abstract : A fractional Kalman filter-based multirate sensor fusion algorithm is presented to fuse the asynchronous measurements of the multirate sensors. Based on the characteristics of multirate and delay measurement, the state is reestimated at the time when the delayed measurement occurs by using weighted fractional Kalman filter, and then the state estimation is updated at the current time when the delayed measurement arrives following the similar pattern of Kalman filter. The simulation examples are given to illustrate the effectiveness of the proposed fusion method.